Ultrasound assessment of diaphragmatic function in type 1 spinal muscular atrophy. Issue 7 (11th May 2020) - Buonsenso, Danilo; Berti, Beatrice; Palermo, Concetta; Leone, Daniela; Ferrantini, Gloria; De Sanctis, Roberto; Onesimo, Roberta; Curatola, Antonietta; Fanelli, Lavinia; Forcina, Nicola; Norcia, Giulia; Carnicella, Sara; et al.
Abstract: Objective: To investigate ultrasound features of diaphragm motion and function in type 1 spinal muscular atrophy (SMA‐1) patients. Design: Prospective study. Patients: The study cohort included SMA‐1 children younger than 18‐year‐old. Control subjects included type 2 and type 3 SMA and other neuromuscular disorders younger than 18‐year‐old. Methodology: Diaphragm ultrasound evaluating diaphragmatic excursion, speed of diaphragmatic contraction, duration of the respiratory cycle, inspiratory/expiratory relationship, end‐inspiratory and ‐expiratory thickness, thickening fraction, and pattern of contractility. The interrater reliability for each variable was established by calculation of Cohen's k coefficient. Results: Twenty‐three SMA‐1 patients and 12 controls were evaluated. Diaphragm ultrasound values were within normal ranges in all study cohort patients and no difference was found with controls. There was a gradient of diaphragm function with SMA 1.9 subgroup having the best and SMA 1.1 having the worst parameters, particularly in end‐inspiratory thickness and diaphragmatic excursion ( P = .031 and P = .041, respectively). Seventy‐four percent of SMA‐1 patients had a dysmotility pattern of diaphragm contraction, mostly represented in SMA 1.9 subgroup ( P = .001). This pattern was observed in 92.8% of children on noninvasive ventilation (NIV) for less than 16 hours/d of and in 20% patients with invasive ventilation or NIV for more than 16 hours/d ( P = .027). The dysmotility pattern was never observed in the control group. The levels of interobserver agreement were high for "diaphragm irregularities, " "inspiratory/expiratory relationship, " and "diaphragm thickness, " and good for the other variables. Conclusions: Ultrasound can be used to evaluate diaphragm function and contractility in SMA‐1 children, providing additional information to the clinical examination and functional respiratory tests, describing a characteristic contractility pattern in these patients. Longitudinal studies are needed to understand the impact of diaphragm dysmotility and other parameters on long‐term outcome in SMA‐1 patients.